Prostaglandin E₂ constrains systemic inflammation through an innate lymphoid cell-IL-22 axis - Duffin, Rodger; O'Connor, Richard A; Crittenden, Siobhan; Forster, Thorsten; Yu, Cunjing; Zheng, Xiaozhong; Smyth, Danielle; Robb, Calum T; Rossi, Fiona; Skouras, Christos; Tang, Shaohui; Richards, James; et al. (Science (American Association for the Advancement of Science), 2016)
Systemic inflammation, which results from the massive release of proinflammatory molecules into the circulatory system, is a major risk factor for severe illness, but the precise mechanisms underlying its control are not fully understood. We observed that prostaglandin E2 (PGE2), through its receptor EP4, is down-regulated in human systemic inflammatory disease. Mice with reduced PGE2 synthesis develop systemic inflammation, associated with translocation of gut bacteria, which can be prevented by treatment with EP4 agonists. Mechanistically, we demonstrate that PGE2-EP4 signaling acts directly on type 3 innate lymphoid cells (ILCs), promoting their homeostasis and driving them to produce interleukin-22 (IL-22). Disruption of the ILC-IL-22 axis impairs PGE2-mediated inhibition of systemic inflammation. Hence, the ILC-IL-22 axis is essential in protecting against gut barrier dysfunction, enabling PGE2-EP4 signaling to impede systemic inflammation.